The Readjustment of Workers Displaced by Plant Shutdowns - Clague, Ewan; Couper, W. J. (Quarterly Journal of Economics, 1931)
Nature of the problem, 309; of the data, 314. — Evidence as to geographical mobility of labor, 316. — Duration of unemployment: before first job, 324; time on first job, 329; time lost during period of survey, 329; unemployed at end of survey, 332: — Quality of jobs obtained, 334. — Change in annual income, 339. — The dismissal wage: purpose, 342; utilization, 343; adequacy, 345.